PROFILE OF MORBIDITY AND MORTALITY IN AT-RISK NEWBORNS - Christine Baccarat de Godoy Martins; Ariane Aguillar Barcelon; Fernanda Cristina Aguiar Lima; Maria Aparecida Munhoz Gaíva (Universidade Federal do Paraná, 2014)
This descriptive study analyzed the profile of morbidity and mortality in the first six months of life among at-risk neonates in Cuiabá in the state of Mato Grosso, in January 2011. The data sources were the Certificate of Live Birth and home interviews held six months after the birth. The study was approved by the Research Ethics Committee and the families signed the Terms of Free and Informed Consent. 113 newborns were studied, of whom 70.8% presented morbidity in the first six months of life, mainly involving respiratory and diarrheal diseases; morbidity was greater among newborns whose mothers did not work outside the home, who were adolescents, or who breast-fed for little time; 5.3% of the children died, of whom 83.3% died in the neonatal period; the deaths occurred more among newborns with low birth weights, or who were premature, or whose mothers did not work outside the home. It is hoped that the results may support specific policies for care to the group composed of live at-risk newborns.